A Tutorial on the Simplification of Electromechanical Dynamic Models - Avanço, Rafael Henrique; Zanella, Danilo Antonio; Cunha, Americo; Tusset, Angelo Marcelo; Balthazar, Jose Manoel [UNESP] (Springer Nature, 2022)
DC motors are electromechanical systems designed to convert electric power to mechanical power. Their dynamics depend on the features of the motor and the load which they move. The dynamics of the motor is influenced by the external loads acting during the rotation. The electromagnetic forces interact according to the mechanical and electric characteristics of the motor. A common procedure is to neglect the effect of inductance in the steady-state speed and constant current. However, a recent analysis in literature claimed the inductance may be highly relevant in some cases in a steady-state regime. However, including the inductance in computer simulations causes highly time-consuming. Therefore, the intention in the present text is to investigate when it is mandatory to consider the motor inductance in the numerical simulation. The conclusion is that the inductance is relevant when the external loads are relatively high and vary in time.